Study on neurotoxicity of dinotefuran, thiamethoxam and imidacloprid against Chinese lizards (Eremias argus). (February 2019) - Wang, Yinghuan; Zhang, Yang; Li, Wei; Han, Yongtao; Guo, Baoyuan
Abstract: The neurotoxicity of dinotefuran, thiamethoxam and imidacloprid against Chinese lizards ( Eremias argus ) were evaluated in acute oral exposure and 28d subchronic exposure. Dinotefuran was not easily metabolized and showed strong persistence in the lizard brain. Thiamethoxam and imidacloprid were rapidly absorbed and excreted in lizards, and were not easily enriched in the lizard brain. Dinotefuran and thiamethoxam could directly increase the concentrations of acetylcholine in the brain and blood by up-regulating the expression of the ach gene, which in turn enhanced the binding of acetylcholine and acetylcholinesterase receptors, eventually causing the release of dopamine. The effect of dinotefuran was more pronounced than thiamethoxam. Clothianidin was a major metabolite of thiamethoxam in the brain and aggravated the neurotoxic effects of thiamethoxam. Imidacloprid desnitro olefin was the only metabolite of imidacloprid that enriched in the brain. The protonation effect of imidacloprid desnitro olefin was stronger than that of the parent imidacloprid, which increased its binding ability to lizard acetylcholinesterase receptors. Competitive inhibition of imidacloprid desnitro olefin and acetylcholine led to the down-regulation of ach gene expression. Although neonicotinoids caused the opening of ligand-gated ion channel through the activation of acetylcholinesterase receptors, the body would alleviate these effects by the inhibition of voltage-dependent channel activity for compensatory mechanisms. This study provided a new perspective on the neotoxic effects of neonicotinoids. Graphical abstract: Highlights: DIN and TMX directly increase the concentrations of ACH in the brain and blood. CLO aggravated the neurotoxic effects of TMX. The formation of IMI-ole-NH caused the down-regulation of the ach gene. Compensatory mechanisms relieve the neurotoxic effects of neonicotinoids.